Parental Perspectives on Private Tutoring in Qatar: Results from the 2019 Qatar Education Study - Hessa Al-Thani; Abdellatif Sellami; Brian Washington Mandikiana (مجلة العلوم التربوية)
The present study sought to identify the factors likely to influence parental use of supplementary private tutoring in the State of Qatar. The study was guided by Hirschman’s concepts of exit, voice, and loyalty embedded in the theory of political science. Drawing on documented international research, a survey was developed to unpack the factors influencing parental use of private tutoring. The study involved 1.142 parents of students in grades 8, 9, 11 and 12 in both public and other (international, community, private Arabic) schools. Using binary probit regression analysis, results derived from this study disclosed five predictors of private tutoring usage among parents. These include the mother’s education level, the student’s school grade, the cost of education-related activities, the type of school a child attends, and the child’s absenteeism from school. The article discusses these results and raises issues that call for attention in local and international educational research. It offers important recommendations for policy and practice.